How Stress Contributes to Workplace Errors and Incidents - Sharma, Ashutosh (Digital Repository of Theses, 2025)
Stress can be defined as a state of mental pressure or concern caused by a difficult, unplanned, or unpleasant situation. These situations can arise from personal, professional, or external factors. These pressures (direct/indirect) are mostly generated from human’s own decisions or external factors that normally humans can’t control. Workplace incidents refer to any unexpected and undesirable events that occur within a work environment. These incidents can range from common workplace accidents like slips, trips, and falls to machinery malfunctions to conflicts between employees. Errors in reports, presentations, and operating machines/equipment can lead to serious accidents, injuries, property damage, or even instances of violence. These incidents can be caused mainly because of four factors: human error, system error, process error, or external factors. Human error is the most variable and causative factor for incidents or errors. Errors caused by humans are mainly due to a lack of knowledge, experience, concentration, or awareness, and stress is one of the most influential factors causing them. Stress can arise from various sources, including work, relationships, financial challenges, health issues, and major life transitions. This study utilized data from both primary and secondary sources to illustrate how stress contributes to workplace errors and incidents. Employees can significantly decrease errors and incidents in both their professional and personal lives by identifying their specific stressors and implementing effective management strategies—such as meditation, healthy eating, exercise, or other stress-reducing activities. Managing stress involves healthy coping strategies such as exercise, relaxation techniques, maintaining a balanced diet, getting enough sleep, and, if required, seeking social or professional support without hesitation. Practicing mindfulness and engaging in activities that bring joy and relaxation can help alleviate stress, reducing errors and incidents. In conclusion, adopting a healthy lifestyle, good time management, adaptive corporate work culture, introducing hybrid working styles, and enhancing employee performance and productivity through training sessions can help reduce stress levels. Reducing constant social media interactions and promoting work-life balance can also contribute to calmer employees and fewer errors and workplace incidents. It is important to remember that stress is not always a negative experience; a certain level of stress can be beneficial as it can motivate individuals to perform at their best.